Sodium sulfite and extrusion affect the nutritional value of soybean products for nursery pigs - L L Burnham; I H Kim; Terry L Gugle; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1994)
A total of 150 weanling pigs (14.2 lb avg body wt) was used in a 28-d growth assay to determine the effects of using sodium sulfite as an extrusion enhancer for soy products. Treatments were: 1) soybean meal (SBM), 2) SBM + sodium sulfite, 3) extruded SBM, 4) SBM extruded with sodium sulfite, 5) extruded whole soybeans, and 6) whole soybeans extruded with sodium sulfite. For d 0 to 14, pigs fed SBM had greater average daily feed intake (ADFD, although they had poorer efficiency of gain (F/G) than pigs fed the extruded soy products. Also, pigs fed sodium sulfite showed a trend for greater average daily gain (ADG) and F/G compared to pigs fed diets without sodium sulfite. The positive response to sodium sulfite continued into Phase II (d 14 to 28), where pigs fed sodium sulfite had greater ADG and ADFI compared to those not fed sodium sulfite. Pigs fed extruded soybeans in Phase II had greater ADG than pigs fed extruded SBM. Overall (d 0 to 28), pigs fed diets with sodium sulfite consumed more feed, gained faster, and tended to have improved efficiencies of gain rompared to those fed diets without sodium sulfite. Also, pigs fed extruded soybeans had greater rates and efficiencies of gain than pigs fed extruded SBM. Thus, in conclusion, sodium sulfite improved growth performance of weanling pigs. Also, extruded soybeans supported greater growth performance than extruded SBM, but pigs fed extruded soybeans responded less to the use of sodium sulfite as an extrusion enhancement than pigs fed the other treatments.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Sodium sulfite; Extrusion; Soybeans; Nursery pigs; Performance